Optimization of Irrigation Schedule for Camelina Sativa, a Biofuel Crop - Kumari, Anuja; Mohsin, Mohammed; Arya, M. C.; Ahmed, P.k. Joshiand Z. (Indian Forester, 2014)
The present study was conducted in the winter season during 2010-12 at Defence Institute of Bio-Energy Research field station- Pithoragarh, Uttarakhand on Camelina sativa cv. Calena to optimize the different levels of irrigation for the large scale multiplication and production of seed for biofuel purposes. Irrigation at early seeding stage and then at preflowering stage resulted in the higher seed yield 1153.61 kg/ha which is 142% higher than control and also gave 472.202 lit/ha of Camelina oil.